The association between the Helicobacter pylori infection and the occurrence of gestational diabetes: a systematic review and meta-analysis - Parisa Kohnepoushi; Rozhin Mansouri; Ali Baradaran Moghaddam; Marzieh Soheili; Hamed Gilzad Kohan; Yousef Moradi (BMC, 2024)
Abstract Background This meta-analysis aims to establish a more precise association between gestational diabetes mellitus (GDM) incidence and H. pylori infection by amalgamating findings from prior case-control and cohort studies. Methods To identify relevant studies, we conducted a comprehensive search using the Excerpta Medica Database (Embase), PubMed (Medline), Web of Science (ISI), and Scopus from January 1990 to November 2022. The screening process involved reviewing the entire text, abstracts, and titles of retrieved articles. Subsequently, data extraction was performed from the selected articles, and their quality was assessed using the Newcastle-Ottawa Scale checklist. Version 17 of STATA software was utilized for the analysis, with relative risks (RR) calculated along with their 95% confidence intervals (CI) to quantify the impact of the included studies. Results This meta-analysis included eight observational and analytical studies. The combined risk of gestational diabetes mellitus (GDM) in pregnant women with H. pylori infection was found to be 1.97 times higher compared to pregnant women without infection (RR: 1.97; 95% CI 1.57-2.47; I2 = 0.00%; P = 0.84). Conclusion Pregnant women with H. pylori infection are at an increased risk of developing gestational diabetes.